2 Statutes at Large of Pennsylvania from 1682 to 1801 ch. 61 sec. 5 at 79 (1896) - (:unkn) unknown (My University, 1700)
"And be it further enacted by the authority aforesaid, That if any negro shall presume to carry any guns, swords, pistols, fowling-pieces, clubs or other arms or weapons whatsoever, without his master's special license for the same, and be convicted thereof before a magistrate, he shall be whipped with twenty-one lashes on his bare back." Passed November 27, 1700; repealed by the Queen in Council, February 7, 1705-6.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES